2022
DOI: 10.17269/s41997-021-00569-6
|View full text |Cite
|
Sign up to set email alerts
|

Quarantots, quarankids, and quaranteens: how research can contribute to mitigating the deleterious impacts of the COVID-19 pandemic on health behaviours and social inequalities while achieving sustainable change

Abstract: The adoption and maintenance of healthy behaviours including age-appropriate amounts of physical activity, limited sedentary and screen time, and healthy eating are the foundations for youth development and thriving. In reviewing extant evidence, we observe that the COVID-19 pandemic has been associated with marked reductions in physical activity, increased sedentary and screen time, and increased food intake and unhealthy snacking. Deleterious effects in movement behaviours appear to be more pronounced among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
8
0
5
Order By: Relevance
“…As school communities try to manage the long‐term impacts of COVID‐19, they require extra support to implement innovative health promotion practices, particularly in disadvantaged areas that have experienced disproportionate health impacts 35 . Schools remain well‐positioned to integrate existing health policy and to continually revise and innovate existing programs to meet the needs of their local communities 39 …”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As school communities try to manage the long‐term impacts of COVID‐19, they require extra support to implement innovative health promotion practices, particularly in disadvantaged areas that have experienced disproportionate health impacts 35 . Schools remain well‐positioned to integrate existing health policy and to continually revise and innovate existing programs to meet the needs of their local communities 39 …”
Section: Findings and Discussionmentioning
confidence: 99%
“…COVID‐19 restrictions have undeniably disrupted the daily routines of children, parents, and teachers, exacerbating the already prevalent physical, behavioral and mental health issues for children and adolescents 39 . The WHO's global status report published in October 2022 indicated that 81% of 11 to 17‐year‐olds are not meeting the recommended daily physical activity guidelines 47 .…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individually, the impacts of the Pandemic and school closures on healthy living behaviours is a major cause for concern, when combined with childhood obesity, the full scale of the problem becomes worryingly apparent. 24 To address the damage that has been done to children by the Pandemic and lockdowns calls have begun for recovery plans for children, see for example Gauvin et al 25 Of course, not just children have suffered from the closure of schools but parents, and particularly mothers, had to take on the responsibility of teachers which many found had a negative impact on their mental health. 26 It would be remiss of researchers to not continue to monitor and assess the long term effects of this period on young people and their families following such an unprecedented compromise of public health.…”
Section: Nr Cluster B Lessons Directly Related To Hlb and Lifestylementioning
confidence: 99%
“…At the same time, the pandemic have also impacted the lives of school-aged children due to restrictions in social interactions with peers and outdoor physical activities during school suspension ( 25 , 26 ). This vulnerable population may be impacted by deterioration in parent-child relations ( 27 ), psychological well-being ( 28 ) or violence and maltreatment ( 29 ).…”
Section: Introductionmentioning
confidence: 99%